Pengembangan Produk Fashion Menggunakan Kertas Bekas Kantong Semen Dengan Pendekatan Low-Impact Use - Astrid Jenifer; Imam Santosa; Imam Damar Djati (JURNAL RUPA, 2019)
Garment material which is processed as a basic material for fashion products is very closely related to environmental problems that occur at this time. By encouraging the idea of sustainability through a low-impact use approach that focuses on the cleaning process, cement bags used paper are made into utilitarian materials that will produce products that cannot be washed. Cement bags used paper have good quality because they can withstand loads of up to 40 kg/sack and are generally used as wrappers or bags that function as covers. However, cement bags used paper tend not to be used or reprocessed into functional products. Therefore, this research aims to design and realize fashion products by recognizing the character and utilizing the potential of cement bags used paper to become products with high use-values. The method used in this research is colouring experiments, testing materials, and exploring shapes and visuals. Material processing is applied using gyre and macrame techniques. The final result of this research is an alternative raw material from cement bags used paper for fashion products.